2007 IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications 2007
DOI: 10.1109/pimrc.2007.4394153
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Two-Priority Network Schema for Single-Buffered Delta Networks

Abstract: In this paper a novel two-priority network schema is presented, and exemplified through its application on singlebuffered Delta Networks in packet switching environments. Network operations considered include conflict resolution and communication strategies. The proposed scheme is evaluated and compared against the single-priority scheme. Performance evaluation was conducted through simulation, due to the complexity of the model, and uniform traffic conditions were considered. Metrics were gathered for the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Figure 10 depicts the normalized throughput of five types of six-stage SeLMINs when multicast ratio is w = 0.5 versus offered load on inputs. The five types of study cases of six-stage single buffered SeLMINs are denoted by the following sets of factors (G S , G F , G L ): (1,2,32), (2,2,16), (3,2,8), (4,2,4) and (5,2,2), respectively. The dot-dashed curve AM-Gs=a% depicts results which are obtained by the analytical method, whereas the solid curve SM-Gs=a% shows results that are obtained by simulation.…”
Section: Normalized Throughput Of a Six-stage Semi-layer Min For Varimentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 depicts the normalized throughput of five types of six-stage SeLMINs when multicast ratio is w = 0.5 versus offered load on inputs. The five types of study cases of six-stage single buffered SeLMINs are denoted by the following sets of factors (G S , G F , G L ): (1,2,32), (2,2,16), (3,2,8), (4,2,4) and (5,2,2), respectively. The dot-dashed curve AM-Gs=a% depicts results which are obtained by the analytical method, whereas the solid curve SM-Gs=a% shows results that are obtained by simulation.…”
Section: Normalized Throughput Of a Six-stage Semi-layer Min For Varimentioning
confidence: 99%
“…video or voice delivery traffic) than non realtime traffic (such as file transfer traffic). Such QoS strategies have been proposed and studied in [4][5][6][7]. Another method to meet QoS requirements is to use MINs that support multicast traffic for servicing a lot of data in a fast manner.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to other approaches [35,36], where priority is defined at the application layer (e.g. real-time packets from streaming media vs. non-real-time packets from file transfer; out-of-band data vs. ordinary TCP traffic and so forth) or in the parallel systems architecture level (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…The same topic is also analyzed by Nasser et al [13] using different approaches. Moreover, Vasiliadis et al [14,15] studied MIN performance evaluation in terms of priority, on finite-buffered MINs with symmetric and asymmetric-sized buffer queues respectively, applying a simulation technique. Also, the findings by Garofalakis et al [6] are typical of what is found when applying analytical techniques to singlelayer multistage networks.…”
Section: Prior Research Studiesmentioning
confidence: 99%